Investigating the Dutch Movement-Specific Reinvestment Scale in people with stroke. (February 2013) - Kleynen, Melanie; Braun, Susy M; Beurskens, Anna JHM; Verbunt, Jeanine A; de Bie, Rob A; Masters, Rich SW
Objective: Reinvestment is a phenomenon in which conscious control of movements that are best controlled automatically disrupts performance. The propensity for reinvestment may therefore play an important role in the movement rehabilitation process. The Movement-Specific Reinvestment Scale measures an individual's propensity for reinvestment. The aim of this study was to translate the scale for use with Dutch participants with stroke and to assess its reliability. Design: A test–retest design. Setting: In community after discharge from rehabilitation centre. Subjects: Forty-five people with stroke. Measures: Reliability of the translated scale was assessed using intraclass correlation coefficients (ICC) and Bland–Altman plot. Results: The ICC was 0.85 (95% confidence interval (CI) 0.74–0.91). Limits of agreement ranged from −2.38 to 3.10. Conclusion: The Dutch Movement-Specific Reinvestment Scale appears to be a reliable tool with which to assess the propensity for movement-specific reinvestment by people with stroke.